The Golden Tree: Guardians of Ga'Hoole - Book 12 - Lasky, Kathryn (New York Scholastic Inc., 2007)
The golden age which is expected from the Great Ga'Hoole Tree turns gradually worse as the owls' young king hunts for the truth about his ancestry. Sequel to: To Be a King
1 - 6
Keywords: Owls - Fiction; Kings and rulers - Fiction; Good and evil - Fiction; Fantasy; Guardians of Ga'Hoole.